(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): To assess knowledge of primary school teachers’ about the stuttering of school-age children at first al-karkh education directorate in Baghdad city, and find out the relationships between primary school teachers’ knowledge and their demographic characteristics. Methodology: The study started from the period of 20th September 2018 to the 1st of March 2020. Probability samples of 370 primary school teachers were chosen randomly. The questionnaire was designed and composed of two parts: the first part deals with the teachers’ demographic data; the second part includes a stuttering knowledge scale. Determined reliability of the questionnaire through a pilot study and determined validity through a panel of (31) experts. The data was collected through the self-administration method was used by asking the participants to complete the format of the questionnaire and fulfill the questions, and it described statistically and analyzed through the use of descriptive and inferential statistical analysis procedures. Results: The findings of the present study indicate that (53.5%) of the study sample have poor knowledge about stuttering of school-age children, and the no-significant relationship between teachers’ demographical characteristics and their knowledge about stuttering. Conclusions: The study concludes that most of the teachers’ had poor knowledge about the stuttering of school-age children, and there are no effects of socio-demographic characteristics of teachers’ on their knowledge about stuttering. Recommendations: The study recommended an education program for primary school teachers about stuttering to improving their knowledge about stuttering in the school environment.